Comment on Syeda Amna Bukhari, et al. (J Pak Med Assoc. 72: 1909-1912, 2022) Comparison of exergaming and vestibular training on gaze stability, balance, and gait performance of older adults: A single blind randomized control trial - Muhammad Tawab Khalil; Farooq Azam Rathore; Imran Irshad (Journal of the Pakistan Medical Association, 2023)
1759 Madam, We have read the article titled “Comparison of exergaming and vestibular training on gaze stability, balance, and gait performance of older adults: A single blind randomized control trial (RCT)” by Bukhari et al with great interest.1. They have correctly highlighted the issue of poor balance and gait instability in the elderly in Pakistan which gets neglected due to lack of training and knowledge for most of the health care professionals and physicians. They used easy and free assessment tools like Dynamic gait index , timed up and go test and Dynamic Visual Acuity Test which can easily be applied in low resource settings like Pakistan. They have used exergaming as a management strategy. This is now widely available in the country commercially and can help patients with balance and gait disorders. We performed a critical analysis of this RCT using Critical Appraisal Skills Programme (CASP) Randomised Controlled Trials Checklist (https:// caspuk. net/wpcontent/uploads/2020/10/CASP_RCT_Checklist _PDF_Fillable_Form.pdf) and The CONSORT (CONsolidated Standards of Reporting Trials) 2010 guidelines.2 In addition, experts have already highlighted certain issues with methodology in rehabilitation trials which were also detected in this article.3 These require clarification and deliberation. Continue..